ERS/TSANZ Task Force Statement on the management of reproduction and pregnancy in women with airways diseases. Issue 2 (6th February 2020) - Middleton, Peter G.; Gade, Elisabeth J.; Aguilera, Cristina; MacKillop, Lucy; Button, Brenda M.; Coleman, Courtney; Johnson, Barbara; Albrechtsen, Charlotte; Edenborough, Frank; Rigau, David; Gibson, Peter G.; Backer, Vibeke
This European Respiratory Society/Thoracic Society of Australia and New Zealand statement outlines a review of the literature and expert opinion concerning the management of reproduction and pregnancy in women with airways diseases: asthma, cystic fibrosis (CF) and non-CF bronchiectasis. Many women with these diseases are now living into reproductive age, with some developing moderate-to-severe impairment of lung function in early adulthood. The statement covers aspects of fertility, management during pregnancy, effects of drugs, issues during delivery and the post-partum period, and patients' views about family planning, pregnancy and parenthood. The statement summarises current knowledge and proposes topics for future research, but does not make specific clinical recommendations. Good management of women with airways diseases before, during and after pregnancy is an important area of respiratory medicine, affecting both the mother and child: a statement from the ERS and TSANZ http://bit.ly/2mMwvGZ